Microleakage evaluation of two types of pit and fissure sealants using two different methods, (in vitro study) - Al-Taie, Lamis A.; Abdul Wahab, Bassam A.; Saeed, Musab H. (Mustansiria Dental Journal, 2018)
Background: Clinical preventive procedures must be done after careful assessment; one of the major risk factor is the occlusal morphology of the posterior teeth. These caries free fissures must be sealed. This in vitro study evaluated the microleakage of two types of sealant materials (unfilled resin and flowable composite) on enamel surfaces prepared using two methods (acid etching with enameloplasty and acid etching alone). Material and methods: Thirty two extracted human third molar were selected and randomly assigned in to 4 groups of eight teeth each; group A, the occlusal surfaces of teeth were acid etched ,then sealed with concise white sealant; group B, they were acid etched then sealed with wave mv flowable composite ;group C, they were prepared with bur ,acid etched ,then sealed with concise white sealant ;group D, they were prepared by bur, acid etched, then sealed with wave mv flowable composite. The sealed surfaces were stored for seven days in distilled water, then specimens were thermocycled 500 cycles, immersed 24 hours in a 2% buffered methylene blue dye, then sectioned and analyzed for leakage under a stereo microscope. Chi-square test was performed to test the differences of leakage among the four groups. Results: The results showed that there was no significant difference (p>0.05) in microleakage for the same material with and without bur preparation. Concise white sealant produced significantly (p<0.05) less microlaekage than wave flowable composite. Conclusion: under the conditions of the present study, bur preparation (enameloplasty) followed by acid etching produces no less microlaekage than did acid etching alone. Concise white sealant (unfilled resin) demonstrated less amount of microlaekage when compared to wave mv flowable composite. Key words: pit and fissure sealant, enameloplasty, unfilled resin, flowable composite